PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MELALUI MINAT BELI PRODUK MS GLOW DI KOTA PEKANBARU - Putri Yuliana Lusi; Aida Nursanti Aida Nursanti; Taufiqurrahman Taufiqurrahman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of product quality and price onpurchasing decisions through interest in buying MS Glow products in the city ofPelabaru. The population in this study was the entire Pekanbaru community whoknew, had used or were currently using Ms Glow products, both men and women,totaling 140 people.Primary data was collected by using a questionnaire as aninstrument to prove the results of the study, to test the hypothesis in this studyusing path analysis (path analysis) with the help of the SPSS program. Thesampling technique that has been selected is the Non-Probality Samplingtechnique where sampling is carried out on the basis of certain objectives orconsiderations.The results of this study indicate that: 1) there is a positive andsignificant effect of product quality on interest in buying MS Glow products in thecity of Pekenbaru, 2) there is a positive and significant effect on price on interestin buying MS Glow products in the city of Pekanbaru, 3) there is a positiveinfluence and significant product quality on purchasing decisions for MS Glowproducts in the city of Pekanbaru, 4) there is a positive and significant influenceon price on purchasing decisions for MS Glow products in Pekanbaru City, 5)there is a positive and significant influence on buying interest on purchasingdecisions for MS Glow products in Pekanbaru City, 6 ) there is a positive andsignificant effect of product quality on purchasing decisions through buyinginterest as an intervening variable for MS Glow products in the city of Pekanbaru,7) there is a positive and significant influence on price on purchasing decisionsthrough buying interest as an intervening variable for MS Glow products in thecity of Pekanbaru. Keywords: Product Quality, Price, Purchase Interest, and Purchase Decision.